Is MRI follow-up relevant in patients with GH-secreting pituitary adenomas primarily treated and responsive to long-acting somatostatin analogues (SMSa)?. Issue 1 (January 2020) - Grandgeorge, Naia; Barchetti, Giovanni; Grunenwald, Solange; Bonneville, Fabrice; Caron, Philippe
Abstract : Objective: Primary SMSa treatment can be associated with hormonal control and tumor shrinkage in patients with GH-secreting pituitary adenomas. The aim of this study was to evaluate whether regular MRI follow-up was necessary in patients with acromegaly-treated and responsive to first-generation long-acting SMSa. Patients and methods: In this retrospective monocentric study we included patients with GH/IGF-1 hypersecretion and pituitary adenomas with normal visual field, primarily treated with first-generation long-acting SMSa between 1995 and 2015 and regularly monitored (clinical evaluation, GH/IGF-1 levels and pituitary MRI) for at least 3 years. Results: We included 83 patients (32 men and 51 women, mean age at diagnosis 50 ± 12 years) with mean GH = 19.3 ± 25.6 ng/mL, IGF-1 = 284 ± 110% ULN and pituitary adenoma height = 12.9 ± 4.7 mm. Mean follow-up was 8.9 ± 4.9 years in 36 controlled patients and 2.0 ± 1.6 years in 47 partial responders to SMSa alone. No significant increase in pituitary adenoma height was observed. Pituitary adenoma height decreased significantly in controlled patients (diagnosis: 11.9 ± 4.8 mm, SMSa: 9.6 ± 3.3 mm, P < 0.001), and in partially responders (diagnosis: 13.6 ± 4.5 mm, SMSa: 11.5 ± 4.5 mm, P < 0.001). Conclusion: During SMSa treatment, no significant increase in GH-secreting adenoma size was observed. Primary SMSa treatment was associated with a significantly decrease in adenoma height in our population. Our cohort data suggest that regular MRI follow-up does not seem relevant in patients with acromegaly who are responsive to SMSa treatment.